2007
DOI: 10.2337/dc07-0922
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness in Pediatric Type 1 Diabetic Patients

Abstract: OBJECTIVE -To compare the carotid artery intima-media thickness in Hispanic pediatric type 1 diabetic patients against that in healthy control subjects matched for age, sex, height, and BMI.RESEARCH DESIGN AND METHODS -The evaluation consisted of anthropometric measurements, biochemical parameters, and a carotid Doppler and real-time ultrasound, in which carotid artery intima-media thickness (cIMT), peak systolic velocity, and end diastolic velocity were measured using standardized procedures.RESULTS -A total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 22 publications
2
36
2
Order By: Relevance
“…4,9,10 The prevalence of cardiovascular diseases in children and adolescents is increasing, and there is evidence that carotid IMT is higher in children with diabetes, hypercholesterolemia and obesity than in healthy controls. 4,5,6,11 Some studies of the effects of exercise training, either associated with dietary changes or alone, showed that weight loss and physical exercise decrease insulin resistance and improve endothelial dysfunction in adults. 12,13 However, few studies have investigated the effects of 1 year of interdisciplinary intervention in this parameter in obese adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…4,9,10 The prevalence of cardiovascular diseases in children and adolescents is increasing, and there is evidence that carotid IMT is higher in children with diabetes, hypercholesterolemia and obesity than in healthy controls. 4,5,6,11 Some studies of the effects of exercise training, either associated with dietary changes or alone, showed that weight loss and physical exercise decrease insulin resistance and improve endothelial dysfunction in adults. 12,13 However, few studies have investigated the effects of 1 year of interdisciplinary intervention in this parameter in obese adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…[93][94][95][96][97] Factors associated with this higher cIMT include lower vitamin C levels 98 and longer duration of disease. 99,100 Adolescents with T2DM also demonstrate higher cIMT compared with healthy control subjects, 101,102 with diabetes mellitus duration 103 and glucose control playing a role.…”
mentioning
confidence: 99%
“…In addition to the researchers in the literature stating that DM increases carotid IMT, there are also researchers reporting no relation 7,15,16,39,40 . In the present study, univariate analyses demonstrated that DM is among the risk factors eff ective on carotid IMT; whereas, regression analysis revealed no signifi cant eff ect of DM on carotid IMT.…”
Section: Resultsmentioning
confidence: 99%